Analisis Perbedaan Skor Plak Gigi Sebelum dan Sesudah Berkumur Air Garam Hangat - Rezki Dirman; Arsad Arsad; Utari Zulkaidah; Yulistina Yulistina; Marwa H Guricci (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
- Dental and oral health is one of the problems in the health sector which is a concern for health workers. Dental and oral health is a part of body health that cannot be separated from one another because dental and oral health will affect holistic body health. Disorders related to dental and oral health are a conflict experienced by most countries in the world. The group of school-aged children is a group that is vulnerable to dental and oral diseases as a result of which it needs to be properly and properly prevented. This study aims to determine differences in dental plaque scores before and after gargling with warm salt water in grades 4, 5 and 6 at UPT SD Negeri 7 Arawa Sidrap Regency in 2023. The type of research used was experimental research with pre-test & post-test methods. . Sampling in this study using stratified random sampling. This sampling technique is carried out by determining the research sample by determining the grouping of members of the population in a group division with a certain level. The results showed that the average score before gargling with salt water was 24.7 and after gargling salt water was 11.8 and the decrease in dental plaque scores before and after gargling with warm salt water was 12.9.